Electrocatalytic alcohol oxidation by a molecular iron complex - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Sen Gupta, Sayam (Faraday Discussions, 2022)
An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe-III-OH2](-), as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe-V(O) species, [(bTAML)Fe-V(O)](-), formed via PCET (overall 2H(+)/2e(-)) from [(bTAML)Fe-III-OH2](-) at 0.77 V (vs. Fc(+)/Fc). Moreover, electrokinetic studies of the oxidation of C-H bonds indicate a second-order reaction, with the C-H abstraction by Fe-V(O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a ``net hydride'' transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a similar to 500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe-IV(O)](2-) species.